Elucidating the mechanisms of vascular dysfunction in obesity and type 2 diabetes: the role of the gut microbiota - Lee, Dustin Michael, author; Gentile, Christopher L., advisor; Weir, Tiffany L., committee member; Johnson, Sarah A., committee member; Chicco, Adam J., committee member (Colorado State University. Libraries, 2019)
One of the key processes that links both obesity and type 2 diabetes (T2D) to cardiovascular disease (CVD) is the development of vascular dysfunction, characterized by arterial stiffness and endothelial dysfunction. Vascular dysfunction occurs prior to overt CVD, and the development of vascular dysfunction in obesity and T2D strongly predicts future cardiovascular events and mortality. While the mechanisms of vascular dysfunction continue to be fully elucidated, an abundant body of research suggests that the gut microbiota mediate many cardiometabolic diseases. Disturbances to microbial equilibrium, broadly termed gut dysbiosis, have been implicated in numerous metabolic disorders. In a proof of concept study, our lab has previously demonstrated that suppression of gut dysbiosis reverses vascular dysfunction. Thus, further identifying useful and cost effective treatments that beneficially target the gut microbiota in obesity or T2D to prevent or reverse vascular dysfunction remains an important area of research. The goals of this dissertation research were to 1) examine the underlying causes of vascular dysfunction in models of obesity and T2D and 2) identify novel strategies to prevent or attenuate the development of vascular dysfunction in both obesity and T2D. To investigate the aforementioned, we conducted three separate preclinical studies utilizing a mouse model of T2D, diet-induced obesity, and gut microbiota transplantation. In these studies, we measured aortic pulse wave velocity and endothelium-dependent dilation to examine arterial stiffness and endothelial dysfunction, respectively. Both of these techniques are clinically relevant. We also employed several biochemical techniques to examine the mechanisms by which obesity and T2D lead to vascular dysfunction in our models. In the first study (Chapter 2), we explored epidemiological data suggesting that the antidiabetic drug class, sodium glucose cotransporter 2 inhibitors (SGLT2i), have beneficial effects on cardiovascular outcomes. Utilizing a genetic model of T2D to examine the vascular effects of SGLT2i, we found that treatment with dapagliflozin significantly improved both arterial stiffness and endothelial function. These changes were accompanied by decreased circulating inflammation and subtle alterations to the gut microbiota. In the second study (Chapter 3), we examined the effect of a gut microbiota-derived tryptophan metabolite on cardiometabolic outcomes. Mice fed a western diet displayed increased body weight, arterial stiffness and elevated markers of liver inflammation. Supplementation with the tryptophan metabolite, indole-3-propionic acid, had no effect on these outcomes. Finally, in the third study (Chapter 4) we examined whether human gut dysbiosis represents a causal factor in obesity-related vascular dysfunction. Utilizing human fecal samples from lean and obese subjects, we found that mice colonized with an obese gut microbiota displayed endothelial dysfunction independent of body weight changes. Collectively, these studies provide evidence that 1) SGLT2i-related cardiovascular protection is in part mediated by improvements in vascular dysfunction, 2) gut microbial metabolites have differing effects on host physiology, and 3) the obese human microbiota promotes endothelial dysfunction independent of body weight. Future studies should examine more mechanistic contributions of the gut microbiota that mediate vascular dysfunction in obesity and type 2 diabetes.